Enceladus's internal ocean and ice shell constrained from Cassini gravity, shape, and libration data. Issue 11 (11th June 2016) - Čadek, Ondřej; Tobie, Gabriel; Van Hoolst, Tim; Massé, Marion; Choblet, Gaël; Lefèvre, Axel; Mitri, Giuseppe; Baland, Rose‐Marie; Běhounková, Marie; Bourgeois, Olivier; Trinh, Anthony
Abstract: The intense plume activity at the South Pole of Enceladus together with the recent detection of libration hints at an internal water ocean underneath the outer ice shell. However, the interpretation of gravity, shape, and libration data leads to contradicting results regarding the depth of ocean/ice interface and the total volume of the ocean. Here we develop an interior structure model consisting of a rocky core, an internal ocean, and an ice shell, which satisfies simultaneously the gravity, shape, and libration data. We show that the data can be reconciled by considering isostatic compensation including the effect of a few hundred meter thick elastic lithosphere. Our model predicts that the core radius is 180–185 km, the ocean density is at least 1030 kg/m 3, and the ice shell is 18–22 km thick on average. The ice thicknesses are reduced at poles decreasing to less than 5 km in the south polar region. Key Points: Gravity, shape, and libration data can be satisfied by models with a 200–400 m elastic lithosphere The ice shell has a variable thickness, 20 km on average and smaller than 5 km at the South Pole Best fit models require an ocean density of at least 1030 kg/m 3 and a core radius of 180–185 km